URBAN AGRICULTURAL PRODUCTION: HEAVY METAL CONTAMINATION OF AMARANTHUS CRUENTUS L. GROWN ON DOMESTIC REFUSE LANDFILL SOILS IN IBADAN, NIGERIA - Sola, Ogunyemi; Opadeji, Taliat Array; Awodoyin, Rasheed O. (Emirates Journal of Food and Agriculture, 2017)
Cultivation of various pot herbs (vegetables) in urban and peri urban centers in Nigeria is a common practice. Many of these cultivated sites serve as waste disposal grounds and the decayed and composted materials portend high soil fertility, hence the common practice of cultivating vegetables on such sites. Lead (Pb) and Cadmium (Cd) concentrations in soils of four Ibadan landfill sites and a control site were determined. The accumulation of these heavy metals in the tissue of Amaranthus cruentus L. was also determined. Analysis of the landfill soil samples showed a range of 110.5 to 678.5ppm for lead and 2.01 to 3.20ppm for cadmium. Different quantities of these metals were recorded in the tissues of Amaranthus cruentus L plants grown on these soils in black polythene bags. Metal accumulation in the plant tissues was found to be proportionate to the level of soil concentrations for Pb while Cd level in the crop tissues exceeded that in the soil. Growth and yield of the crop were significantly reduced due to Pb and Cd contamination of the soil. It is concluded that Ibadan landfills are unsafe for Amaranthus cruentus cultivation. The concentrations of the heavy metals found in the tissues of the vegetable grown on the landfills were much higher than the optimum allowed by FAO/WHO for dietary consumption